From the solution of the expression, it can be seen that s = 6 when t = 3 while t = 1 when s = 2.
<h3>How do we solve a mathematical expression?</h3>
Given:
(12t) = (6s) ........................ (1)
When t = 3, we can solve for s from the expression in equation (1) by substituting t = 3 into the equation as follows:
12 * 3 = 6s
36 = 6s
s = 36 / 6
s = 6
When s = 2, we can solve for t from the expression in equation (1) by substituting s = 2 into the equation as follows:
12t = 6 * 2
12t = 12
t = 12 / 12
t = 1
Learn more about mathematical expression here: brainly.com/question/12401681.
#SPJ1
Answer:
(11, 12)
Step-by-step explanation:
<u>Mid point coordinates:</u>
- x = (x₁ + x₂)/2
- y = (y₁ + y₂)/2
<u>Since midpoint and one endpoint given (10, 4) and (9, -4), the other endpoint:</u>
- x₂ = 2x - x₁ = 2*10 - 9 = 11
- y₂ = 2y - y₁ = 2*4 - (-4) = 12
<u>So the other endpoint is: </u>(11, 12)
Answer:
Width: 15 Length: 53
Step-by-step explanation:
-9-6i/-3-2i
Factor -3 out of expression
-3(3+2i)/-3-2i
Then extract the negative sign out of the expression
-3(3+2i)/-(3+2i)
Reduce the fraction with -(3+2i)
-3/-1
-3*-1=3
Hope this helps
Maybe it was (7-2x)/-4+2<-x then times 4 both sides
<span>
</span>
-7+2x+8<-4x
<span>
</span>
2x+1<-4x
<span>
</span>
6x+1<0
<span>
</span>
6x<-1
<span>
</span>
x<-1/6
<span>
</span>
there we go